2021
DOI: 10.24198/jkg.v33i3.35696
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perawatan ortodonti dan bedah open window impaksi gigi insisif permanen pertama rahang atas</p><p>Orthodontic treatment and open window surgery of impacted maxillary first permanent incisor</p>

Abstract: Impaksi gigi insisif sentral rahang atas merupakan kasus yang sering menjadi keluhan estetika pasien. Impaksi gigi insisif sentral rahang atas memerlukan perawatan multidipliner oleh ortodontis, spesialis bedah mulut dan periodontis. Perawatan bedah dapat dilakukan secara open window atau closed window bergantung kasus. Tujuan laporan kasus ini untuk memaparkan perawatan impaksi gigi 11 karena adanya odontoma di tepi insisal gigi 11 menggunakan alat ortodonti cekat dan bedah open window. Laporan kasus: Seorang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[ 9 ] Multidisciplinary treatment usually is required in treating this case. [ 11 12 ] A multidisciplinary approach increases the horizons of treatment to meet the expectations of the patient. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Multidisciplinary treatment usually is required in treating this case. [ 11 12 ] A multidisciplinary approach increases the horizons of treatment to meet the expectations of the patient. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the position of the mental foramen indirectly determines the success of treatment. 1,3,5,6,[14][15][16][17][18][19][20][21] Based on research by Thakare, et al (2016) conducted on the population of Pune, central India, with a sample of 100 men and 100 women who had the results of 48% in men and 52% in women, the position of the mental foramen was located in line with the second premolar. The study concluded that there was no difference in the distribution of the position of the mental foramen based on gender.…”
Section: Introductionmentioning
confidence: 99%